“OLD” IDEAS IN NEW SOCIAL CONTEXT. UNIVERSITY AND CHALLENGES OF THE GLOBAL MARKET OF EDUCATIONAL “SERVICES” - Charchuła, Jarosław (The Modern Higher Education Review, 2021)
The level of education is an increasingly important factor that determines both social-economic changes and the systems of norms and values. On the one hand, globalization processes offer the richness and variety of the goods of culture, and the access to “broad” knowledge. On the other hand, they reinforce the tendency for unification and standardization of many areas in an individual’s life. In order to properly refer to modern changes a university is subject to, we should trace historical changes that affected this institution and analyse modern expectations that are shaped by the global market of services. This article focuses on the analysis of the process of science globalization. Such approach to science is characterized by the analysis of features that define science as a social institution. In this context, the most important challenges and difficulties related to the specific features of the global exchange market have been presented.